ORGANIZATION OF CLOUD COMPUTING INFRASTRUCTURE BASED ON SDN NETWORK - Alexey A. Efimenko; Sergey V. Fedoseev (Статистика и экономика)
The article presents the main approaches to cloud computing infrastructure based on the SDN network in present data processing centers (DPC). The main indexes of management effectiveness of network infrastructure of DPC are determined. The examples of solutions for the creation of virtual network devices are provided.